2016
DOI: 10.1177/1359105314566256
|View full text |Cite
|
Sign up to set email alerts
|

The influence of optimism on functionality after total hip replacement surgery

Abstract: Among other factors, optimism has been shown to significantly influence the course of some diseases (cancer, HIV, coronary heart disease). This study investigated whether optimism of a patient before a total hip replacement can predict the functionality of the lower limbs 3 and 6 months after surgery. A total of 325 patients took part in the study (age: 58.7 years; w: 55%). The functionality was measured with the Western Ontario and McMaster Universities arthrosis index, and optimism with the Life Orientation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…An additional regression analysis on the impact of the difference between patient-reported EQ-5D VAS and EHS-based valuation on postoperative WOMAC sum indicated that high patient-reported values compared to average population values correlate positively with knee specific outcomes (Additional file 8: Table S8). If relatively high, pre-operative VAS reports by patients would be interpreted as a sign of optimism, this result would resemble improved outcomes found for optimistic patients after hip replacement [48].…”
Section: Discussionmentioning
confidence: 99%
“…An additional regression analysis on the impact of the difference between patient-reported EQ-5D VAS and EHS-based valuation on postoperative WOMAC sum indicated that high patient-reported values compared to average population values correlate positively with knee specific outcomes (Additional file 8: Table S8). If relatively high, pre-operative VAS reports by patients would be interpreted as a sign of optimism, this result would resemble improved outcomes found for optimistic patients after hip replacement [48].…”
Section: Discussionmentioning
confidence: 99%
“…Following this initial review, 46 full-texts were assessed for eligibility of which 20 manuscripts were excluded for at least one of the following reasons: non-significant findings (n = 6) 1,10,48,56,58,63 , the analyses/results were not relevant to review hypotheses (n = 6) 6,9,20,35,42,90 , and the critical test statistic was not reported, could not be computed based on reported data, and could not be obtained after contact with the author (n = 3) 3,18,86 (see Figure 1). The latter criterion included studies reporting pvalue ranges (e.g.…”
Section: Study Selection and Search Criteriamentioning
confidence: 99%
“…Alternatively, we could have employed the validated Hospital for Special Surgery (HSS) Hip and Knee Replacement Expectations Survey comprising 18 items informed by the ICF-framework [72,73]. However, the German, culturally adapted version of this questionnaire had not been validated until 2016 and was not available at the time of the planning and data collection of our study [74]. Future investigations should make use of the existing validated surveys of expectations and de ne which aspect of the construct they would like to address in order to obtain more reliable, comparable and accurate results.…”
Section: Limitationsmentioning
confidence: 99%